Design and Analysis of Combined Vibration Absorbers for Ship Propulsion Shaft Systems - Dongdong Luo; Qing Ouyang; Hongsheng Hu (Actuators)
The vibration of a ship’s propulsion shaft system directly affects the ship’s lifespan, and many studies have designed vibration absorbers only for one of the natural frequencies of a ship’s propulsion shaft system without considering the influence of multiple low-order resonance frequencies. In this paper, a vibration absorber combined with a magnetorheological elastomer vibration absorber and a rubber vibration absorber in series is designed, and it can cover two torsional natural frequency band ranges to achieve better vibration reduction performances in multiple different torsional natural frequencies. The torsional natural frequency of the propulsion shafting of a 45 m fishing vessel is determined based on a multiple-degrees-of-freedom equivalent discretization model. Two natural frequencies, 22.4 Hz and 131.4 Hz, of a ship propulsion shaft system are selected as the design goal parameters of the combined vibration absorber. The magnetic field is simulated to ensure that the magnetic field generated by an energized coil can meet requirements. Then, a dynamic simulation of the ship propulsion shaft system with a combined vibration absorber is conducted via co-simulation. Afterward, the device is installed on the intermediate shaft of the ship propulsion shaft system for simulation, and the vibration reduction effect of the device is analyzed at different frequencies by controlling the current. When the device is controlled to operate at the optimal frequency point, the results show that the angular acceleration vibration amplitude reduction around the first and third torsional natural frequencies of the propulsion shaft system reaches 90% and 18%, respectively. This study provides new ideas for the intelligent and controllable vibration damping of ship propulsion shaft systems, especially for the development trend of intelligent ship equipment under complex working conditions.